SALO, a novel classical pathway complement inhibitor from saliva of the sand fly Lutzomyia longipalpis - Ferreira, Viviana P; Fazito Vale, Vladimir; Pangburn, Michael K; Abdeladhim, Maha; Mendes-Sousa, Antonio Ferreira; Coutinho-Abreu, Iliano V; Rasouli, Manoochehr; Brandt, Elizabeth A; Meneses, Claudio; Lima, Kolyvan Ferreira; Nascimento Araújo, Ricardo; Pereira, Marcos Horácio; et al. (Scientific reports, 2016)
Blood-feeding insects inject potent salivary components including complement inhibitors into their host's skin to acquire a blood meal. Sand fly saliva was shown to inhibit the classical pathway of complement; however, the molecular identity of the inhibitor remains unknown. Here, we identified SALO as the classical pathway complement inhibitor. SALO, an 11 kDa protein, has no homology to proteins of any other organism apart from New World sand flies. rSALO anti-complement activity has the same chromatographic properties as the Lu. longipalpis salivary gland homogenate (SGH)counterparts and anti-rSALO antibodies blocked the classical pathway complement activity of rSALO and SGH. Both rSALO and SGH inhibited C4b deposition and cleavage of C4. rSALO, however, did not inhibit the protease activity of C1s nor the enzymatic activity of factor Xa, uPA, thrombin, kallikrein, trypsin and plasmin. Importantly, rSALO did not inhibit the alternative or the lectin pathway of complement. In conclusion our data shows that SALO is a specific classical pathway complement inhibitor present in the saliva of Lu. longipalpis. Importantly, due to its small size and specificity, SALO may offer a therapeutic alternative for complement classical pathway-mediated pathogenic effects in human diseases.
Keywords: Recombinant Proteins; Complement C4; komplement 4; lidé; Humans; komplement C1; Complement Inactivating Agents; Psychodidae; Animals; hmyzí proteiny; Saliva; zvířata; vysokoúčinná kapalinová chromatografie; rekombinantní proteiny; sliny; klasická dráha komplementu; Complement C1; Complement Pathway, Classical; Insect Proteins; inhibitory komplementu; Chromatography, High Pressure Liquid; aktivace komplementu; Complement Activation